Investigating the impacts of ChatGPT on students motivation in learning English grammar - Gunawan, Florencia Cindy; Susanto, Allvian Ika Fiki (Journal of English Language Teaching and Learning (JETLE), 2025)
Nowadays, technology has developed and greatly influenced the world of education, one of which is an AI called ChatGPT. This AI is very widely used today, but its influence certainly raises the pros and cons of its users. Therefore, this study aims to explore students' perceptions of the impact of ChatGPT on their motivation to learn grammar. This study used a mixed-methods research design, combining quantitative and qualitative approaches through questionnaires and interviews. The objects of the study were 25 students majoring in English from 5 different universities in Central Java, Indonesia. The data obtained will be statistically analyzed using the average system of each sub-theme. The findings of the study revealed that students generally have a positive perception of ChatGPT's role in increasing their motivation to learn grammar. However, the study also identified two main issues: the sometimes-inaccurate feedback from ChatGPT and students' tendency to become overly dependent on the tool.